Lymph Fasciocutaneous Lateral Thoracic Artery Flap: Anatomical Study and Clinical Use - Barreiro, Guilherme Cardinali; Baptista, Rachel Rossine; Kasai, Kiril Endo; dos Anjos, Daniel Marchi; Busnardo, Fabio de Freitas; Modolin, Miguel; Ferreira, Marcus Castro (Journal of Reconstructive Microsurgery, 2014)
Background The lateral thoracic flap was first studied in the mid-1970s but its use has been limited because of pedicle anatomical variations. However, after the development of lymph node transfer surgery, the axilla/upper lateral thorax presented as a promising donor area. Through a detailed anatomical study, the lateral thoracic flap was evaluated regarding its vascularization and composition. Later, it was used for pedicle and free flap reconstructions.Methods A total of 40 flaps were dissected in fresh cadavers and the characteristics of the lateral thoracic pedicle and its relationship to the upper lateral thoracic axillary lymph nodes (LTLN) were analyzed. We performed six pedicle flap reconstructions around the shoulder area and a free lymph node transfer for lower limb lymphedema.Results In the cadaveric dissections, the lateral thoracic pedicle branched off the axillary vessels and was found to be a primary level I axillary lymph node irrigator before reaching the skin. The cutaneous portion of the artery was present in 87.5% of the dissections. Arterial caliber was an average of 1.3 and venous, 2.6 mm. Five to seven lymph nodes were isolated with each pedicle and a lymph fasciocutaneous flap could be designed. In seven clinical cases, all of the flaps survived. Functioning lymph nodes were visualized on lymphoscintigraphy after their transfer to the ankle. Donor area had an inconspicuous evolution.Conclusion Lateral thoracic flap is a feasible flap with low donor area morbidity in a concealed region that can be harvested with upper LTLN for transplantation.
Keywords: lateral thoracic flap; lymph fasciocutaneous flap; lateral thoracic artery; lymph node transfer; lymphedema